1998
DOI: 10.1111/j.1750-3639.1998.tb00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Factors Deactivate Antigen Presenting Cells that Invade the Central Nervous System

Abstract: We hypothesized that CNS tissue has the potential to deactivate invading monocytes/macrophages in order to maintain the immune privilege of the brain, and furthermore, that astrocytes are the cells that initiate monocyte/macrophage deactivation. To test this hypothesis, fluorescent prelabeled rat spleen macrophages with typical amoeboid morphology were transferred into organotypic hippocampal slice cultures (OHSCs), where they gradually developed a ramified morphology similar to the appearance of resting micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Some researchers suggest that soluble ICAM-1 might compete for receptors of membrane bound ICAM-1 and effectively inhibit aging related increases in immune responses in the brain (Hailer et al, 1998). Such a role would be consistent with comparatively good cognitive performance detected in elderly subjects even when they have high levels of ICAM-1 (Elwan et al, 2003).…”
Section: Discussionmentioning
confidence: 88%
“…Some researchers suggest that soluble ICAM-1 might compete for receptors of membrane bound ICAM-1 and effectively inhibit aging related increases in immune responses in the brain (Hailer et al, 1998). Such a role would be consistent with comparatively good cognitive performance detected in elderly subjects even when they have high levels of ICAM-1 (Elwan et al, 2003).…”
Section: Discussionmentioning
confidence: 88%
“…It has been known for many years that astrocytes are capable of modulating microglial/macrophage function. They have been shown to modulate LPS-induced changes in inducible nitric oxide synthase and NO production (28, 29) and expression of MHCII (30), effects that have been attributed to astrocytic release of soluble factors like transforming growth factor TGF␤. The present findings uncover another mechanism by which astrocytes can modulate microglial activation.…”
Section: Discussionmentioning
confidence: 99%
“…The following pro-and antiinflammatory molecules, which have been shown to convey potent effects on CNS inflammatory reactions, were applied to the culture system: (1) TNF-a, which is preferentially produced by cells of the macrophage lineage including microglia, and known to be one of the most active proinflammatory mediators under a variety of inflammatory conditions (Larrick andWright 1990, Chabot et al, 1997); (2) IL-1b, which plays an important role in initiating immune responses and has been found to activate lymphocytes and microglia (Dinarello, 1991); (3) IL-6, which exerts proinflammatory activity like acute-phase responses and B-cell stimulation, but also possesses antiinflammatory characteristics, such as restraining the inflammatory and demyelinating processes in MS (Stelmasiak et al, 2001); (4) the proinflammatory cytokine IFN-g, which is secreted by macrophages and activated T lymphocytes in MS lesions, where its level of secretion correlates with the disability status of MS patients (Petereit et al, 2000); it also induces class II MHC antigen expression in monocytes and astrocytes (Porrini and Reder 1994); (5) two antiinflammatory substances TGF-b1 and IFN-b. TGF-b1, besides its multiple effect on T-cell suppression, MHC class II downregulation and deactivation of macrophages (Hailer et al, 1998) has been found to exert a robust downregulation of the production of proinflammatory cytokines in the brain (Khoury et al, 1992), while IFN-b has been proved to promote the secretion of endogenous antiinflammatory cytokines like TGF-b1 and IL-10 (Porrini et al, 1995;Ossege et al, 1999). These effects have made IL-10 one of the most common cytokines in the treatment of MS, together with IFN-b (Rudick et al, 1996).…”
Section: Introductionmentioning
confidence: 99%